The dynamic role of small- and medium-sized multinationals in global production networks: Norwegian maritime firms in the Greater Shanghai Region in China - Amdam, Rolv Petter; Bjarnar, Ove; Wang, Jinmin (Taylor & Francis, 2018)
This article examines the role of small- and medium-sized multinational enterprises (MNEs) in the dynamic development of global production networks (GPNs) in the maritime industry. It studies the dynamism between subsidiaries of Norwegian maritime firms and regional actors and institutions in the Greater Shanghai Region of China from the perspectives of the subsidiaries. It argues that strategic coupling, recoupling and decoupling are partly the results of regional selection mechanisms. However, in the cases where the subsidiaries are embedded within the host region, the strategies and behaviour of MNEs are of decisive importance for the dynamic development of GPNs.